First host record of Myopa pellucida Robineau-Desvoidy (Diptera: Conopidae) identified using DNA barcoding - Smit, John; Raemakers, Ivo; Beentjes, Kevin (Zootaxa, 2018)
Thick-headed flies of the genus Myopa Fabricius are a common sight in early spring in Europe. Several species can be found flying among Salix catkins together with their supposed Andrena Fabricius hosts (Hymenoptera: Apidae) (John Smit observations). Despite the fact that some of these Myopa species are very common, little is known about their actual host-parasitoid associations. Only a few scattered host records can be found in the literature, most of which refer to M. testacea s.l.. Whether or not these records actually concern M. testacea (Linnaeus) is uncertain due to the confusion over the identity of several species within the M. testacea species group (Stuke & Clements 2008). Stuke (2017), in his World Catalogue of Conopids, provides all recorded host associations and distinguishes between unambiguously accepted host records and doubtful records based on three criteria: 1) the conopid has been reared from the host or a larva has been identified by DNA barcoding; 2) there is no doubt concerning the identity of the conopid species concerned, and 3) there is no doubt concerning the identity of the host species. Because the vast majority of the host records in the literature do not fulfil one or more of these criteria they are regarded as doubtful (Stuke 2017). Thus, only three host associations for the genus Myopa can be regarded as confirmed: Andrena vaga Panzer, for both M. hirsuta Stuke & Clements (Jentzsch 2009) and M. testacea (Erteld 1998, Fellendorf et al. 2004, De Meijere 1912), and the Nearctic Andrena regularis Malloch, for the Holarctic M. vicaria Walker (Miliczky & Osgood 1995). Here we report on a fourth host association for the genus Myopa, since a second instar larva of M. pellucida Robineau-Desvoidy was found in the abdomen of an Andrena nitida (Müller) female and identified using DNA barcoding.